The Whitaker Test in the Follow-up of Complex Upper Urinary Tract Reconstruction: Is It Clinical Useful or Not - Li, Xinfei; Yang, Kunlin; Zhu, Weijie; Chen, Yuke; Yang, Yang; Zhang, Peng; Wu, Juan; Wu, Pengjie; Wu, Shiliang; Li, Xuesong; Zhou, Liqun (Urology Journal, 2021)
Purpose: To evaluate the feasibility and guiding significance in postoperative management of the Whitaker test after complex reconstruction of the upper urinary tract. Materials and Methods: Patients who underwent complex ureteral reconstruction and received the Whitaker test after surgery between December 2018 and December 2019 were included. We judged it abnormal that the renal pelvis pressure was higher than 22 cmH2O or the pressure difference was greater than 15 cmH2O. The results were used as a reference for removing the nephrostomy tube. Based on whether the renal pelvic pressure was higher than 22 cmH2O, the patients were divided into the elevated pelvis pressure group and the normal group. Follow ups at 1 month and every 3 months were collected. Results: A total of 19 patients were included. Fifteen patients did not present obvious abnormalities. One patient suffered from contrast infiltrating into the renal parenchyma, and the pressure was higher than 15 cmH2O. Ureteral stent implantation was performed. The other 3 patients had either elevated pelvis pressure or insufficient image, 2 of which prolonged the duration of nephrostomy tubes. The median follow-up time was 12.6 months. CTU/MRU after removing nephrostomy tubes indicated improved/stable hydronephrosis in all patients. The creatinine in the elevated pelvis pressure group was higher than that in the normal group (91.4 ± 27.6 vs 86.7 ± 16.5 μmol/L, P = .782), and the eGFR was lower (76.0 ± 14.0 vs 81.8 ± 24.1 mL/min/1.73m2, P = .695), but without significant difference. The change in creatinine during follow-up in the elevated renal pelvic pressure group was significantly different from that in the normal group (-13.6 ± 1.0 vs -0.2 ± 10.6 umol/L, P = .047). Conclusion: Postoperative Whitaker test can help judge whether nephrostomy could be removed. Elevated pressure in upper urinary tract after reconstruction suggests the need to prolong the time of the nephrostomy tube or even re-intervene. Proper management for patients with elevated renal pelvis pressure can help restore the renal function.